IMMUNOLOGICAL ASPECTS OF INFANTS AND YOUNG CHILD FEEDING IN EMERGENCY SITUATIONS - Назаренко, Ірина; Громова, Тетяна; Коваленко, Поліна (SWorldJournal, 2023)
The article discribes advantages of feeding infants and young children with mother’s breast milk, special attention is paid to immune factors as components of breast milk. The need for infants to consume mother’s breast milk is noted due to the underdeve